Lactational Vitamin E Protects Against the Histotoxic Effects of Systemically Administered Vanadium in Neonatal Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: The work investigated the protective role of lactational vitamin E administration on vanadium-induced histotoxicity. Three groups of Wistar rats, with each group comprising of two dams and their pups, were used in this study. Group I pups were administered intraperitoneal injection of sterile water at volumes corresponding to the dose rate of the vanadium (sodium metavanadate) treated group from postnatal day (PND) 1-14 while those in Group II were administered intraperitoneal injection of 3mg/kg vanadium from PND 1-14. Group III pups were administered intraperitoneal injection of 3mg/kg vanadium while the dam received oral vitamin E (500mg) concurrently every 72hours. The results showed that group II pups exhibited histopathological changes which included seminiferous tubule disruption of the testes characterised by vacuolar degeneration and coagulative necrosis of spermatogonia and Sertoli cells with reduction in mitosis, and areas of interstitial thickening with fibroblast proliferation. In addition, the lungs showed disruption of the bronchiolar wall and denudation of the bronchiolar respiratory epithelium while the liver showed hydropic degeneration and coagulative necrosis of the centrilobular hepatocytes. These histotoxic changes were ameliorated in the vanadium + vitamin E group. We conclude that lactational vitamin E protects against the histotoxic effects of vanadium and could be a consideration for supplementation in the occupationally and environmentally exposed neonates. However, caution should be taken in vitamin E supplementation because there is still equivocal evidence surrounding its benefits as a supplement at the moment.
Keywords: Vanadium; Vitamin E; Histotoxicity; Antioxidant